2018
DOI: 10.1002/2211-5463.12407
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 is essential for ectodomain shedding of the EGF‐receptor ligand amphiregulin

Abstract: The epidermal growth factor (EGF)‐receptor ligand amphiregulin (AREG) is a potent growth factor implicated in proliferative skin diseases and in primary and metastatic epithelial cancers. AREG, synthesized as a propeptide, requires conversion to an active peptide by metalloproteases by a process known as ectodomain shedding. Although (ADAM17) a disintegrin and metalloprotease 17 is a key sheddase of AREG, ADAM8‐, ADAM15‐, and batimastat (broad metalloprotease inhibitor)‐sensitive metalloproteases have also bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
0
28
2
Order By: Relevance
“…166 EGFR immunoreactivity is demonstrable in the peripheral layer of human SGs, the interfollicular epidermis, outer root sheath and eccrine sweat gland. 167,168 Ectopic activation of Egfr signalling in mouse epidermis results in enlarged, hyperproliferative SGs [169][170][171][172][173][174][175][176] and increased sebum production ( Table 2). 174 Expansion of the Lrig1-expressing compartment has also been observed upon overexpression of epigen, an Egfr ligand, in mouse epidermis (Table 2).…”
Section: Erbb Family Receptor Signallingmentioning
confidence: 99%
“…166 EGFR immunoreactivity is demonstrable in the peripheral layer of human SGs, the interfollicular epidermis, outer root sheath and eccrine sweat gland. 167,168 Ectopic activation of Egfr signalling in mouse epidermis results in enlarged, hyperproliferative SGs [169][170][171][172][173][174][175][176] and increased sebum production ( Table 2). 174 Expansion of the Lrig1-expressing compartment has also been observed upon overexpression of epigen, an Egfr ligand, in mouse epidermis (Table 2).…”
Section: Erbb Family Receptor Signallingmentioning
confidence: 99%
“…Mouse models of human disease have long served a valuable role in biomedical research. In recent years, we have generated and validated mice carrying the human TOC disease mutation p.P189L ( Hosur et al, 2017a ; Figure 1A , top panel, Figure 1B ), characterized a spontaneous mutation that results in a TOC phenotype ( Hosur et al, 2014 ), and used these mouse models of TOC in studies in which we identified AREG as a functional driver of the disease ( Hosur et al, 2014 , 2017a ); established an essential role for ADAM17 in mediating the disease ( Hosur et al, 2018 ); and, most recently, demonstrated that RHBDF2-AREG-EGFR signaling, and not the immune system or surrounding microenvironment, plays a role in mediating the disease ( Hosur et al, 2017b ). These and other murine models of TOC ( Table 1 ) will be useful for methodically studying the molecular pathways underlying TOC in further detail, for investigating the molecular pathways underlying related proliferative skin diseases, and for testing novel and existing therapeutics.…”
Section: Murine Modelsmentioning
confidence: 99%
“…However, in studies using Rhbdf2 cub/cub mice, we ( Hosur et al, 2014 ) and others ( Leilei et al, 2014 ; Siggs et al, 2014 ) found that ADAM17 activity is reduced in Rhbdf2 cub/cub mice, suggesting that RHBDF2 regulates secretion of AREG independently of ADAM17 activity. Thus, to examine whether RHBDF2 participates directly in shedding of EGFR ligands, similarly to ADAM17, we generated Rhbdf2 cub/cub mice with ADAM17-deficient keratinocytes ( Rhbdf2 cub/cub Adam17 flox/flox K14-Cre ) and studied their phenotype ( Hosur et al, 2018 ). We found that ADAM17 deficiency in the skin of Rhbdf2 cub/cub mice restored a full hair coat and impaired the rapid wound-healing phenotype observed in Rhbdf2 cub/cub mice, demonstrating that ADAM17 is the major ectodomain sheddase of AREG and that RHBDF2 does not directly participate in the shedding of AREG.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…The syndrome is characterized by palmar and plantar hyperkeratosis, accelerated wound healing, oral leukoplakia, and a markedly elevated risk of developing esophageal squamous cell carcinoma [ 58 , 98 , 99 , 100 , 101 , 102 , 103 ]. In mouse models of the syndrome it was shown that deletion of the EGFR ligand AR or ADAM17 were able to restore normal skin phenotype [ 137 , 138 ] and that the defect was skin specific [ 139 ]. While this cancer syndrome is extremely rare it gave us important insights into the iRhom2-EGFR relationship.…”
Section: Irhom2 Regulated Pathwaysmentioning
confidence: 99%